Super-hydrophilic and super-oleophobic oil-water separation membrane and preparation method thereof
By constructing superhydrophilic -O-Ti-F- groups on porous titanium foam and treating the surface roughness, a highly efficient and stable superhydrophilic and superoleophobic oil-water separation membrane was prepared, solving the problems of low oil-water separation efficiency and insufficient stability in the existing technology, and achieving rapid and environmentally friendly oil-water separation effect.
Patent Information
- Application Number
- CN202211556835.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-06
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2042-12-06
AI Technical Summary
Existing oil-water separation membranes suffer from low oil-water separation efficiency, insufficient stability, and inadequate mechanical strength, failing to meet practical application requirements.
Using porous titanium foam as the substrate, a superhydrophilic -O-Ti-F- group is constructed by hydrothermal reaction with low-concentration HF. The surface roughness is increased by infrared laser treatment to prepare a superhydrophilic and superoleophobic oil-water separation membrane.
The prepared oil-water separation membrane has high mechanical strength, fast separation speed and good stability. It can effectively separate oil-water mixtures and is environmentally friendly with no secondary pollution, making it suitable for the field of oil-water separation.
Smart Images

Figure CN115999378B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to an oil-water separation membrane, specifically a superhydrophilic and superoleophobic oil-water separation membrane and its preparation method, belonging to the field of superhydrophilic materials. Background Technology
[0002] The separation of oil-water mixtures has long been a hot academic topic and also has significant practical industrial demand in order to address increasingly serious environmental pollution problems, such as oil spills and oily wastewater discharge. Traditional oil-water separation methods (such as centrifugation, suspension, and sedimentation) suffer from high energy consumption in centrifugation and low efficiency in suspension and sedimentation methods. Therefore, emerging methods based on the surface energy difference between oil and water are considered more environmentally friendly, efficient, and economical. The oil-water separation problem is essentially an interface problem, and the most direct way to effectively improve separation efficiency is to prepare separation materials with superoleophobic or superhydrophobic surfaces. However, existing oil-water separation membranes generally suffer from low separation efficiency, low stability, and low mechanical strength, failing to meet practical applications. Summary of the Invention
[0003] The technical problem to be solved by the present invention is to overcome the existing technical defects and provide an oil-water separation membrane with high mechanical strength, fast separation speed and good stability, as well as a preparation method thereof.
[0004] To solve the above-mentioned technical problems, the present invention provides a superhydrophilic and superoleophobic oil-water separation membrane, comprising a substrate and superhydrophilic groups modified on the surface of the substrate;
[0005] The substrate is porous titanium foam, and the superhydrophilic group is an -O-Ti-F- group.
[0006] In this invention, the -O-Ti-F- group is constructed by hydrothermal reaction of low concentration HF with a foamed titanium substrate.
[0007] In this invention, the concentration of the HF solution is 0.05-0.1%.
[0008] This invention also provides a method for preparing the above-mentioned superhydrophilic and superoleophobic oil-water separation membrane, specifically including the following steps:
[0009] S1. Pretreatment of titanium substrate with metal foam;
[0010] S2. The -O-Ti-F- group is constructed by hydrothermal reaction of low-concentration HF and metal foam titanium substrate;
[0011] S3. Dry the reacted substrate to obtain a superhydrophilic and superoleophobic oil-water separation membrane.
[0012] In this invention, step S1 includes:
[0013] S1.1 The substrate is ultrasonically cleaned sequentially with acetone, ethanol, and deionized water;
[0014] S1.2 Then, an infrared laser is used to perform surface cladding on the substrate;
[0015] S1.3 Finally, the substrate is immersed in hydrochloric acid solution and heated to react, removing the oxides on the substrate surface.
[0016] In this invention, the substrate is ultrasonically cleaned sequentially in acetone, anhydrous ethanol, and deionized water for 10 minutes.
[0017] In this invention, the infrared laser has a power of 27-54W and a scanning speed of 200-400mm / s.
[0018] In this invention, the concentration of the hydrochloric acid solution is 15-19%.
[0019] In this invention, step S2 includes: the concentration of the HF solution is 0.05-0.1%, the hydrothermal reaction temperature is 100-140℃, and the reaction time is 1-4h.
[0020] The beneficial effects of this invention are as follows: (1) An oil-water separation membrane with fine -O-Ti-F- groups on the surface is obtained by modifying titanium foam using a simple one-step hydrothermal method. Titanium foam is a porous metal foam material with high porosity and good mechanical strength, and it is easy to react with HF. While further increasing the surface roughness of the substrate, its surface energy is also increased, giving the titanium foam substrate superhydrophilic and superoleophobic properties. Its underwater oil contact angle can reach 161°, so water will form a stable water film on the substrate surface and prevent oil droplets from passing through, thereby achieving a good oil-water separation effect. (2) The titanium foam separation membrane has good chemical stability and can be recycled multiple times, avoiding secondary pollution to the environment. By using a one-step hydrothermal method, a fine -O-Ti-F- rough structure group is generated on the surface, thereby increasing the surface energy and constructing a superhydrophilic and superoleophobic modified titanium foam, which can be applied to the field of oil-water separation. (3) Using an infrared laser to treat the surface of the substrate can increase the surface roughness of the titanium foam substrate, providing a favorable foundation for subsequent group construction. (4) Soaking the substrate in hydrochloric acid can effectively remove oxide layer impurities from the substrate surface. (5) The HF solution concentration is 0.1%, the hydrothermal reaction temperature is 120℃, and the reaction time is 4h. Too short a reaction time is not conducive to the formation of -O-Ti-F- groups, while too long a reaction time will result in overly coarse group structures. (6) Experiments have shown that the oil-water separation membrane of the present invention can effectively separate oil-water mixtures of n-hexane, petroleum ether, vegetable oil, and xylene, and has good separation efficiency. It has advantages such as high porosity, fast separation speed, high separation efficiency, stable performance, and high mechanical strength. Moreover, the preparation process is simple, low-cost, and environmentally friendly. Attached Figure Description
[0021] Figure 1 FESEM images of titanium foam before and after hydrothermal treatment;
[0022] Figure 2 A comparison of the underwater oil droplet adhesion of raw foamed titanium and hydrothermally treated foamed titanium.
[0023] Figure 3 The contact angle and roll-off angle of titanium foam placed under different environments are shown in the diagram.
[0024] Figure 4 The graph shows the filtration efficiency of hydrothermally treated titanium foam for n-hexane, vegetable oil, xylene, and petroleum ether.
[0025] Figure 5 The graph shows the filtration efficiency of unwashed and washed titanium foam after hydrothermal treatment. Detailed Implementation
[0026] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The components of the embodiments of the present invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations.
[0027] Therefore, the following detailed description of the embodiments of the invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the invention without inventive effort are within the scope of protection of the invention.
[0028] The following detailed description of some embodiments of the present invention is provided in conjunction with the accompanying drawings. Unless otherwise specified, the following embodiments and features can be combined with each other.
[0029] The technical principle of this invention is as follows: A specially designed oil-water separation membrane offers high separation efficiency and is reusable, achieving separation of oil-water mixtures solely under gravity. The preparation of this superhydrophilic and superoleophobic separation membrane requires exhibiting extremely low surface adhesion to oil droplets to effectively prevent surface contamination. In practical applications, for most oil-water mixtures, the oil droplet density is lower than that of water. Under gravity, water preferentially contacts the membrane surface and penetrates downwards. Due to the membrane's superhydrophilicity, a water film forms on its surface, preventing oil droplets from passing through, thus achieving separation. In this invention, HF is used as a fluorine source and reactant to construct a high-surface-energy superhydrophilic and superoleophobic rough structure on the surface of titanium foam, resulting in a low-cost, high-efficiency, and stable oil-water separation membrane. This membrane does not generate secondary pollution during separation and is particularly suitable for situations with high water content and low oil content. It is a truly anti-fouling, economical, durable, and highly efficient oil-water separation membrane.
[0030] In the following examples, the substrate selected is titanium foam. Titanium foam is an environmentally friendly porous metal foam material with advantages such as high mechanical strength, high separation accuracy, strong reusability, good corrosion resistance, and small pore size. Metal materials are relatively reactive and easy to modify on the surface, making titanium foam an ideal substrate for preparing superhydrophilic oil-water separation membranes.
[0031] Example 1
[0032] Step 1: Cut the metal foam titanium board to obtain the metal foam titanium substrate.
[0033] Step 2, pretreatment of the titanium foam substrate:
[0034] The cut metal foam titanium substrate was ultrasonically cleaned for 10 minutes each with acetone, anhydrous ethanol and deionized water. After cleaning, it was dried in a forced-air drying oven for 20 minutes to remove organic stains from the surface of the metal foam titanium substrate.
[0035] Then, an infrared laser was used to scan the cleaned and dried titanium foam substrate. The laser power was set to 27W and the scanning speed was 400mm / s. The front and back sides of the titanium foam substrate were scanned once each to increase the surface roughness of the titanium foam substrate and provide more group growth sites for the subsequent hydrothermal reaction.
[0036] Next, the titanium foam substrate is immersed in a 19% hydrochloric acid solution at 80°C and heated in a water bath for 15 minutes. Afterward, it is rinsed with deionized water and dried at 90°C to obtain the pretreated titanium foam substrate. In this step, immersing the substrate in hydrochloric acid effectively removes oxide layer impurities from the surface of the titanium foam substrate.
[0037] Step 3, hydrothermal reaction: Prepare a 0.1% HF solution, then transfer it to a PTFE-lined reactor. The pretreated titanium foam substrate is then vertically immersed in the solution and reacted at 120°C for 4 hours to construct -O-Ti-F- groups on the surface of the titanium foam substrate. In this step, if the HF solution concentration is too low, the reaction on the substrate surface will not be sufficient to form a uniform group structure; if the HF solution concentration is too high, the reaction will be too vigorous and easily destroy the already formed surface group structure. Similarly, if the reaction time is too short, it will not be conducive to the formation of -O-Ti-F- groups; if the time is too long, the group structure will be too coarse, affecting the final group formation effect.
[0038] Step 4: Remove the reacted titanium foam substrate, rinse with deionized water for 30 seconds, and then dry in an oven at 60°C for 2 hours to obtain a superhydrophilic and superoleophobic oil-water separation membrane.
[0039] Verification of the effect of Example 1:
[0040] The morphology of the oil-water separation membrane obtained in Example 1 was observed and compared using a scanning electron microscope, such as... Figure 1 As shown. Figure 1 In the images, a represents the original titanium foam, which has a very smooth surface with virtually no micro- or nano-scale rough structures; b represents the pretreated titanium foam, which has wavy patterns on its surface, caused by laser cladding, which increases the surface roughness and provides favorable conditions for the growth of -O-Ti-F- groups; c and d represent titanium foam after hydrothermal treatment at different ratios, showing that fine -O-Ti-F- groups have grown on its surface, with individual protruding structures measuring approximately 200-300 nm.
[0041] Comparative analysis of the contact angles of pristine and hydrothermally treated titanium foam surfaces reveals that the aggregation of -O-Ti-F- groups significantly affects the wettability of the titanium foam surface. Furthermore, the adhesion of oil to the surface of the oil-water separation membrane directly impacts its filtration efficiency and antifouling performance. Figure 2 As shown, the experiment tested the adhesion of raw and hydrothermally treated titanium foam to dichloromethane underwater, demonstrating the process of a 5 μL oil droplet approaching, contacting, being compressed, and rising from the surface. For raw titanium foam, the oil droplet spreads out rapidly upon contact, indicating that raw titanium foam is oleophilic underwater and does not possess oil-water separation properties (see ad). However, when the oil droplet contacts the hydrothermally treated titanium foam surface, the needle continues to descend and compress the droplet, causing it to deform. When the needle slowly rises, the droplet easily leaves the surface of the hydrothermally treated titanium foam without leaving any smaller droplets (see a1-d1). In summary, hydrothermally treated titanium foam exhibits very low adhesion to oil droplets, and its wettability changes from oleophilic underwater to superoleophobic underwater.
[0042] like Figure 3 As shown, the stability of the oil-water separation membrane was tested. Oily wastewater typically contains a certain amount of acids, alkalis, and salts; therefore, resistance to corrosion by these substances is a significant challenge for oil-water separation membranes and a crucial indicator of their stability. To investigate the stability of the oil-water separation membrane, it was placed in various environments for 24 hours before contact angle and roll-off angle tests were performed. The membrane was placed in air, water, sodium hydroxide solution, hydrochloric acid solution, and sodium chloride solution for 24 hours respectively, and the contact angle and roll-off angle were measured. Figure 3 As shown in the figure, it can be seen that when the OCA20 contact angle meter is used for testing, the oil-water contact angle of the oil-water separator can reach up to 161°.
[0043] like Figure 4 As shown, an oil-water separation test was performed. 15 mL of hexane, petroleum ether, vegetable oil, xylene, and 15 mL of water were mixed to form an oil-water mixture. The oil-water separation membrane prepared in Example 1 was sandwiched between the separation instruments for oil-water separation, and the mass of water before and after separation was recorded.
[0044] The oil-water separation efficiency is calculated using the following formula:
[0045] η(%) = M2 / M1 × 100%;
[0046] Where M1 is the initial mass of water before separation, and M2 is the mass of water after separation. The separation efficiency η is the average of multiple measurements (3 times). The influence of different types of oils on the oil-water separation membrane efficiency was analyzed, and the results are as follows: Figure 4 As shown, the separation efficiency of hydrothermally treated titanium foam for hexane, petroleum ether, and xylene is all above 99%. However, vegetable oil, due to its higher viscosity, is more likely to clog the filter pores, thus reducing the filtration efficiency, although the filtration efficiency is still greater than 97%.
[0047] To test the reusability of the oil-water separation membrane, a circulating filtration experiment was conducted using n-hexane, petroleum ether, vegetable oil, and xylene. The experimental results are as follows: Figure 5 As shown, the filtration efficiency of an unwashed oil-water separator gradually decreases with each filtration cycle. This is because oil droplets continuously accumulate on the surface of the oil-water separator, clogging the filter pores and affecting filtration efficiency. However, after cleaning the oil-water separator with anhydrous ethanol every four filtrations, the oil on the membrane is removed, and the filtration efficiency returns to its original level.
[0048] Example 2
[0049] Step 1 is the same as in Example 1.
[0050] Step 2, pretreatment of the titanium foam substrate:
[0051] The cut metal foam titanium substrate was ultrasonically cleaned for 11 minutes each with acetone, anhydrous ethanol and deionized water. After cleaning, it was dried in a forced-air drying oven for 10 minutes to remove organic stains from the surface of the metal foam titanium substrate.
[0052] Then, an infrared laser was used to scan the cleaned and dried metal foam titanium substrate. The laser power was set to 44W and the scanning speed was 310mm / s. The front and back sides of the metal foam titanium substrate were scanned once each.
[0053] Next, the titanium foam substrate was immersed in a 15% hydrochloric acid solution at a temperature of 72°C. After reacting in a water bath for 13 minutes, it was rinsed with deionized water and dried at a temperature of 100°C to obtain the pretreated titanium foam substrate.
[0054] Step 3, hydrothermal reaction: Prepare a 0.05% HF solution, then transfer it to the liner of a polytetrafluoroethylene reactor, and then vertically immerse the pretreated metal foam titanium substrate in it, and react at 100°C for 3 hours to construct -O-Ti-F- groups on the surface of the metal foam titanium substrate.
[0055] Step 4: Remove the reacted titanium foam substrate, rinse with deionized water for 20 seconds, and then dry in an oven at 70°C for 2 hours to obtain a superhydrophilic and superoleophobic oil-water separation membrane.
[0056] Example 3
[0057] Step 1 is the same as in Example 1.
[0058] Step 2, pretreatment of the titanium foam substrate:
[0059] The cut metal foam titanium substrate was ultrasonically cleaned for 9 minutes each with acetone, anhydrous ethanol and deionized water. After cleaning, it was dried in a forced-air drying oven for 16 minutes to remove organic stains from the surface of the metal foam titanium substrate.
[0060] Then, an infrared laser was used to scan the cleaned and dried metal foam titanium substrate. The laser power was set to 54W and the scanning speed was 200mm / s. The front and back sides of the metal foam titanium substrate were scanned once each.
[0061] Next, the titanium foam substrate was immersed in a 17% hydrochloric acid solution at a temperature of 60°C. After reacting in a water bath for 10 minutes, it was rinsed with deionized water and dried at a temperature of 60°C to obtain the pretreated titanium foam substrate.
[0062] Step 3, hydrothermal reaction: Prepare a 0.08% HF solution, then transfer it to the PVC reactor liner, and vertically immerse the pretreated titanium foam substrate in it. React at 140°C for 1 hour to construct -O-Ti-F- groups on the surface of the titanium foam substrate.
[0063] Step 4: Remove the reacted titanium foam substrate, rinse with deionized water for 10 seconds, and then dry in an oven at 80°C for 1 hour to obtain a superhydrophilic and superoleophobic oil-water separation membrane.
[0064] The above description is only a preferred embodiment of the present invention. It should be noted that those skilled in the art can make several improvements without departing from the principle of the present invention, and these improvements should also be considered within the scope of protection of the present invention.
Claims
1. A superhydrophilic and superoleophobic oil-water separation membrane, characterized in that: It includes a substrate and superhydrophilic groups modified on the surface of the substrate; the substrate is porous titanium foam, and the superhydrophilic groups are -O-Ti-F- groups; The substrate was ultrasonically cleaned sequentially with acetone, ethanol, and deionized water. Then, the substrate is surface treated with an infrared laser. Specifically, the cleaned and dried metal foam titanium substrate is laser scanned with an infrared laser. The laser power is set to 27W and the scanning speed is 400mm / s. The front and back sides of the metal foam titanium substrate are scanned once each to increase the surface roughness of the metal foam titanium substrate. Finally, the substrate is immersed in hydrochloric acid solution and heated to react, removing the oxides on the substrate surface; The -O-Ti-F- group is constructed by hydrothermal reaction of low concentration HF with porous titanium foam.
2. The superhydrophilic and superoleophobic oil-water separation membrane according to claim 1, characterized in that: The concentration of the HF solution is 0.05-0.1%.
3. The method for preparing the superhydrophilic and superoleophobic oil-water separation membrane according to claim 1 or 2, characterized in that... Includes the following steps: S1. Pretreatment of titanium foam substrate: The substrate is ultrasonically cleaned sequentially with acetone, ethanol and deionized water; Then, the substrate is surface treated with an infrared laser. Specifically, the cleaned and dried metal foam titanium substrate is laser scanned with an infrared laser. The laser power is set to 27W and the scanning speed is 400mm / s. The front and back sides of the metal foam titanium substrate are scanned once each to increase the surface roughness of the metal foam titanium substrate. Finally, the substrate is immersed in hydrochloric acid solution and heated to react, removing the oxides on the substrate surface; S2. The -O-Ti-F- group is constructed by hydrothermal reaction of low-concentration HF and metal foam titanium substrate; S3. Dry the reacted substrate to obtain a superhydrophilic and superoleophobic oil-water separation membrane.
4. The method for preparing the superhydrophilic and superoleophobic oil-water separation membrane according to claim 3, characterized in that: The substrate is ultrasonically cleaned sequentially in acetone, anhydrous ethanol, and deionized water for 9-11 minutes each.
5. The method for preparing the superhydrophilic and superoleophobic oil-water separation membrane according to claim 3, characterized in that: The concentration of the hydrochloric acid solution is 15-19%.
6. The method for preparing the superhydrophilic and superoleophobic oil-water separation membrane according to claim 3, characterized in that... Step S2 includes: the concentration of the HF solution is 0.05-0.1%, the hydrothermal reaction temperature is 100-140℃, and the reaction time is 1-4h.
Citation Information
Patent Citations
Preparation method of titanium alloy bionic super-hydrophobic surface
CN113278958A
